Scale-up of Aspergillus ibericus lipase production by solid-state fermentation - Oliveira, Felisbela Maria Araújo (2015)
This work deals with the production of lipase by Aspergillus ibericus under solid state fermentation (SSF) of olive pomace (OP) with wheat bran (WB) at packed-bed, tray-type and pressurized bioreactors. Moreover, the effect of the sterilization step of the residues on lipase activity was studied. The sterilization at 121ºC of residues benefits lipase production. SSF scale-up from flasks to different bioreactors was successfully performed with a slight lipase production decrease from 27% to 40% of the total lipase units produced per mass of residue in Erlenmeyer´s flasks using autoclaved residues (183 ± 21 U/g). Contrariwise, results of specific activity obtained in flasks (51 ± 4 U/mg) were similar to the obtained in the packed-bed bioreactor (using autoclaved residues) and in the pressurized bioreactor (using no autoclaved residues).